Electrospinning Fabrication Methods to Incorporate Laminin in Polycaprolactone for Kidney Tissue Engineering - Büsra Baskapan; Anthony Callanan (Tissue Engineering and Regenerative Medicine, 2022)
BACKGROUND : Today’s treatment options for renal diseases fall behind the need, as the number of patients has increased considerably over the last few decades. Tissue engineering (TE) is one avenue which may provide a new approach for renal disease treatment. This involves creating a niche where seeded cells can function in an intended way. One approach to TE is combining natural extracellular matrix proteins with synthetic polymers, which has been shown to have many positives, yet a little is understood in kidney. Herein, we investigate the incorporation of laminin into polycaprolactone electrospun scaffolds. METHOD : The scaffolds were enriched with laminin via either direct blending with polymer solution or in a form of emulsion with a surfactant. Renal epithelial cells (RC-124) were cultured on scaffolds up to 21 days. RESULTS : Mechanical characterization demonstrated that the addition of the protein changed Young’s modulus of polymeric fibres. Cell viability and DNA quantification tests revealed the capability of the scaffolds to maintain cell survival up to 3 weeks in culture. Gene expression analysis indicated healthy cells via three key markers. CONCLUSION : Our results show the importance of hybrid scaffolds for kidney tissue engineering.

3D human liver tissue from pluripotent stem cells displays stable phenotype in vitro and supports compromised liver function in vivo - Hassan Rashidi; Nguyet-Thin Luu; Salamah M. Alwahsh; Maaria Ginai; Sharmin Alhaque; Hua Dong; Rute A. Tomaz; Bertrand Vernay; Vasanthy Vigneswara; John M. Hallett; Anil Chandrashekran; Anil Dhawan; et al. (Archives of Toxicology, 2018)

A Non-woven Path: Electrospun Poly(lactic acid) Scaffolds for Kidney Tissue Engineering - Todd P. Burton; Anthony Callanan (Tissue Engineering and Regenerative Medicine, 2018)

From Tension to Compression: Asymmetric Mechanical Behaviour of Trabecular Bone’s Organic Phase - Shuqiao Xie; Robert J. Wallace; Anthony Callanan; Pankaj Pankaj (Annals of Biomedical Engineering, 2018)